Method for storing recovered bis (2-hydroxyethyl) terephthalate and method for producing polyester resin
By mixing the recovered bis(2-hydroxyethyl)terephthalate with solvent and storing it at a specific temperature, the problem of quality deterioration of the recycled substance during storage is solved, and the effect of improving the color quality of the polyester resin is achieved. .
Patent Information
- Application Number
- CN202380047446.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-23
- Filing Date
- 2023-06-15
- Publication Date
- 2025-02-07
AI Technical Summary
The quality of the recovered bis(2-hydroxyethyl)terephthalate may deteriorate during storage, affecting the quality of the final polyester resin.
The recovered bis(2-hydroxyethyl)terephthalate was mixed with a solvent to prepare a solution with a concentration of 95% by weight or less and stored at a temperature of 120°C or less to maintain the yellow index at 2 or lower level.
By this method, the purity and yellow index of the recovered bis(2-hydroxyethyl)terephthalate can be stably maintained, thereby improving the color quality of the final polyester resin.
Smart Images

Figure BDA0005190081520000171 
Figure BDA0005190081520000231 
Figure BDA0005190081520000241
Abstract
Description
Technical Field
[0001] The present invention relates to a storage method of recovered bis(2-hydroxyethyl)terephthalate and a method for preparing a polyester resin. In addition, the present invention relates to a polyester resin prepared by the above method and a product containing the polyester resin. Background Art
[0002] Polyester is widely used in beverage filling containers, packaging films, audio-visual films and other materials due to its excellent mechanical strength, heat resistance, transparency and gas barrier properties. In addition, polyester is widely produced worldwide as an industrial material such as medical fiber and tire cord. In particular, polyester sheets or plates have good transparency and excellent mechanical strength, so they are widely used as raw materials for boxes, boxes, partitions, shelves, panels, packaging materials, building materials, interior and exterior materials, etc.
[0003] As a result, the amount of plastic waste such as polyester generated worldwide each year has reached an uncontrollable level. Recently, countries around the world are formulating regulations and plans for the recycling of waste plastic resources, including waste polyester. For example, attempts have been made to use a certain percentage or higher of recycled resin in packaging materials used in various fields. Although physical or chemical methods are used as methods for recycling waste polyester, physical recycling methods cannot guarantee purity and are therefore not widely used.
[0004] In the chemical recycling method, the ester bonds of the waste polyester are cleaved to depolymerize it. Reactions such as glycolysis, hydrolysis, methanolysis and aminolysis are used. Glycolysis is the decomposition of the waste polyester at high temperature by adding glycols such as ethylene glycol or diethylene glycol. A reaction product containing mainly bis(2-hydroxyethyl)terephthalate (BHET) is obtained. After crystallization or purification, bis(2-hydroxyethyl)terephthalate can be used as a raw material for the preparation of unsaturated polyesters or ester polyols.
[0005] In this regard, Korean Patent No. 1386683 discloses a crystallization method and apparatus for chemical recovery of waste polyester. U.S. Patent No. 7211193 discloses a method for purifying bis(2-hydroxyethyl) terephthalate (BHET), which comprises treating a main component of poly(2-hydroxyethyl) terephthalate with ethylene glycol (EG). Polyester of ethylene glycol formate (PET) is decomposed The resulting solution solidifies under certain temperature conditions. crystallization and solid-liquid separation.
[0006] [Prior art literature]
[0007] (Patent Document 1) Korean Patent No. 1386683,
[0008] (Patent Document 2) U.S. Patent No. 7,211,193. Summary of the invention
[0009] Technical issues
[0010] The recovered bis(2-hydroxyethyl)terephthalate obtained by depolymerizing waste polyester can be stored for a period of time and then used in the polymerization of polyester resin. During the storage period, the quality of the recovered BHET may deteriorate, in which case the quality of the final polyester resin may be affected.
[0011] The present inventors have found that when the recovered bis(2-hydroxyethyl)terephthalate is mixed with a solvent and stored under specific conditions, the purity and yellowness index can be stably maintained, and the color and other qualities of the final polyester resin produced therefrom can be correspondingly improved.
[0012] Therefore, an object of the present invention is to provide a method for stably storing a recovered bis(2-hydroxyethyl)terephthalate solution, and a method for preparing a high-quality polyester resin using the method.
[0013] Solution to the problem
[0014] According to the present invention, there is provided a method for storing recovered bis(2-hydroxyethyl)terephthalate, which comprises (1) mixing recovered bis(2-hydroxyethyl)terephthalate obtained by depolymerizing waste polyester with a solvent to prepare a solution of recovered bis(2-hydroxyethyl)terephthalate having a concentration of 95 wt % or less; and (2) storing the recovered bis(2-hydroxyethyl)terephthalate solution at a temperature of 120° C. or less to maintain a YID index of 2 or less as defined below:
[0015] YID index = (YID - YID [Day 0]) / YID [Day 0]
[0016] Here, YID[day 0] is the yellowness index of the bis(2-hydroxyethyl)terephthalate solution recovered 30 minutes after the preparation in step (1), and YID is the yellowness index of the bis(2-hydroxyethyl)terephthalate solution recovered after the storage in step (2).
[0017] In addition, according to the present invention, there is provided a method for preparing a polyester resin, the method comprising using According to the above The polyester resin is polymerized from recycled bis(2-hydroxyethyl)terephthalate stored in the process.
[0018] Furthermore, according to the present invention, there is provided a polyester resin comprising the recycled bis(2-hydroxyethyl)terephthalate stored according to the above method.
[0019] Furthermore, according to the present invention, there is provided an article comprising the polyester resin.
[0020] Advantageous Effects of the Invention
[0021] According to the present invention, the recovered bis(2-hydroxyethyl)terephthalate obtained by depolymerizing waste polyester is mixed with a solvent and stored under specific temperature and concentration conditions to suppress the deterioration of purity and yellow index. Therefore, the quality, such as color, of the final polyester resin prepared therefrom can be improved.
[0022] Specifically, according to the present invention, since the purity and yellowness index of the recovered BHET solution are very little changed even after being stored for a certain period of time, the color quality of the final polyester resin obtained therefrom is hardly deteriorated even if it is used for polymerization reaction after being stored for a certain period of time.
[0023] Therefore, the recycled BHET stored according to the present invention and the polyester resin prepared therefrom can be used to prepare articles made of environmentally friendly materials in various fields.
[0024] Best Mode for Carrying Out the Invention
[0025] The present invention will be described in more detail below.
[0026] In the present specification, the terms relating to each component are used to distinguish them from each other, and are not intended to limit the scope of the embodiment. In addition, in the present specification, a singular expression is also interpreted as covering the plural, unless the context indicates otherwise.
[0027] In this specification, the terms first, second, etc. are used to describe various components. However, these components should not be limited by these terms. These terms are used to distinguish one element from another.
[0028] In this specification, the term "comprising" is intended to specify specific features, regions, steps, methods, elements and / or components. Unless otherwise expressly stated, the existence or addition of any other features, regions, steps, methods, elements and / or components is not excluded.
[0029] Recycled bis(2-hydroxyethyl)terephthalate
[0030] Bis(2-hydroxyethyl)terephthalate is an ester of two ethylene glycols and one terephthalic acid. For example, it is a compound formed as an intermediate in the process of preparing polyesters such as polyethylene terephthalate (PET) by polymerization of ethylene glycol and terephthalic acid or its esters.
[0031] According to the present invention, bis(2-hydroxyethyl)terephthalate used as a raw material for polyester resin polymerization (BHET) is obtained from waste polyester having repeating units of ethylene glycol and terephthalic acid, such as polyethylene terephthalate (PET) or ethylene glycol-modified polyethylene terephthalate (PETG), and can be obtained, for example, by known depolymerization methods such as glycolysis, hydrolysis, and methanolysis.
[0032] The bis(2-hydroxyethyl)terephthalate (BHET) obtained by depolymerization of waste polyester as described above is referred to as "recycled bis(2-hydroxyethyl)terephthalate (recycled BHET)", or abbreviated as r-BHET or rBHET, which should be understood to be different from pure BHET compounds.
[0033] Specifically, the recovered BHET may contain reagents or solvents used in various chemical steps during the depolymerization of waste polyester or by-products formed by side reactions with them. Therefore, the BHET recovered by the common depolymerization process contains organic and inorganic impurities in addition to BHET as the main component. Therefore, the recovered BHET can also be regarded as a composition containing two or more components, namely a BHET composition. It can be used as a polymerization raw material for producing polyester resin.
[0034] The impurities contained in the recovered BHET may include, for example, diethylene glycol derivatives and unreacted monomers. The total content of impurities contained in the recovered BHET may be 10 wt % or more, 15 wt % or more, or 20 wt % or more, and may be 40 wt % or less, 35 wt % or less, 30 wt % or less, or 25 wt % or less.
[0035] The purity of recovered BHET can be measured using liquid chromatography, etc. Specifically, the purity of recovered BHET can be calculated by measuring the fraction (%) of the peak area of BHET to the total peak area in a spectrum obtained using high performance liquid chromatography (HPLC).
[0036] For example, the purity of the recovered BHET can be 99.9% or less, 99% or less, 95% or less, 90% or less or 85% or less, and can be 60% or more, 65% or more, 70% or more, 75% or more or 80% or more. Specifically, the purity of the BHET added to the transesterification reaction of the present invention can be 60% to 99.9%, more specifically, 65% to 99% or 70% to 99%.
[0037] In addition, in a 25 wt% solution, the yellowness index (YID) of the recovered bis(2-hydroxyethyl)terephthalate measured using a spectrophotometer may be 3.0 or less. Specifically, the yellowness index may be 2.5 or less, 2.0 or less, 1.5 or less, or 1.0 or less.
[0038] Although the bis(2-hydroxyethyl)terephthalate used in the present invention can be depolymerized by conventional methods To prepare, However, it can also be prepared by carrying out the depolymerization reaction in multiple steps in order to reduce the impurities,For example, diethylene glycol ester can be used to obtain higher purity. Specifically, bis(2-hydroxyethyl)terephthalate can be obtained by performing a depolymerization reaction in multiple steps while significantly reducing the temperature of the next step, and then performing ion exchange and distilling unreacted ethylene glycol after the depolymerization reaction.
[0039] According to one embodiment, a method for preparing recycled bis(2-hydroxyethyl)terephthalate may include (1a) depolymerizing waste polyester by a first glycolysis reaction at a temperature of 180°C to 200°C to obtain a first reactant; (1b) depolymerizing the first reactant by a second glycolysis reaction at a temperature of 150°C to 170°C to obtain a second reactant; (1c) ion exchanging the second reactant by an ion exchange resin to obtain a third reactant; (1d) removing unreacted ethylene glycol from the third reactant by distillation at a temperature of 150°C or less to obtain a fourth reactant; and (1e) distilling the fourth reactant to obtain crude bis(2-hydroxyethyl)terephthalate.
[0040] According to a specific embodiment, first, waste polyester is pulverized to a size of 4 mm or less for use, ethylene glycol is added thereto, and then, in the presence of a zinc acetate catalyst, a first glycolysis reaction is performed at a temperature of 180° C. to 200° C. for about 2 hours, and ethylene glycol is further added thereto, and then, at a temperature of 150° C. to 170° C., a second glycolysis reaction is performed for about 2 hours. Thereafter, it is cooled to 120° C. or less using reduced pressure flash evaporation, a small amount of filter aid is added thereto, and then it is filtered to separate insoluble foreign matter by solid-liquid separation, and it is passed through a column filled with an ion exchange resin to perform ion exchange. Then, unreacted ethylene glycol is recovered at a temperature of 100° C. to 130° C., purified by thin film evaporation at 190° C. to 250° C., and finally, an adsorption-crystallization step is performed to obtain high-purity and high-quality bis(2-hydroxyethyl)terephthalate.
[0041] According to the above method, two steps of glycolysis reaction (i.e., the first glycolysis reaction and the second glycolysis reaction) are performed. If the solvation is accelerated in the first glycolysis reaction, the transesterification reaction of the waste polyester in the second glycolysis reaction can be carried out under the conditions of lower temperature and shorter reaction time. Therefore, the concentration of diethylene glycol (DEG) naturally formed at the ordinary glycolysis reaction temperature can be significantly reduced, and the content of diethylene glycol ester in the finally prepared bis(2-hydroxyethyl) terephthalate can be significantly reduced.
[0042] Preparation and storage of recovered bis(2-hydroxyethyl)terephthalate solution
[0043] The recovered bis(2-hydroxyethyl)terephthalate (BHET) may be stored for a period of time before being used in the polymerization of the polyester resin.
[0044] Since the recycled BHET is obtained by depolymerizing waste polyester, many side reactions may occur compared to newly synthesized high-purity BHET monomer, depending on storage conditions such as temperature. As a result, the quality of the recycled BHET may deteriorate depending on the storage conditions before being put into the polymerization reaction, in which case the quality of the polyester resin may eventually be affected. If such deteriorated recycled BHET is used, the quality of the final polyester resin may be impaired.
[0045] According to the present invention, when the recovered BHET is mixed with a solvent to prepare a solution having a specific concentration range and then stored within a specific temperature range, the generation of byproducts that may affect the color quality of the final polyester resin can be suppressed to ensure storage stability. Thereafter, a polymerization reaction is performed using the recovered BHET solution stored in the above manner, thereby finally obtaining a high-quality polyester resin while ensuring process stability during its feeding.
[0046] First, the recovered BHET is mixed with a solvent to prepare a solution of the recovered BHET having a concentration of 95 wt % or less. Within the above concentration range, it is beneficial to maintain the quality of the recovered BHET solution during storage and improve the performance of the polyester resin prepared therefrom. For example, the concentration of the recovered BHET solution can be 90 wt % or less, 85 wt % or less, 80 wt % or less, 75 wt % or less, 70 wt % or less, 65 wt % or less, 60 wt % or less, or 55 wt % or less, and can be 5 wt % or more, 10 wt % or more, 15 wt % or more, 20 wt % or more, 25 wt % or more, 30 wt % or more, 35 wt % or more, 40 wt % or more, or 45 wt % or more. As a specific example, the concentration of the recovered BHET solution can be 5 wt % to 95 wt %, 5 wt % to 55 wt %, 45 wt % to 95 wt %, or 25 wt % to 95 wt %.
[0047] Examples of solvents for preparing the recovered BHET solution include water, ethylene glycol, methanol and ethanol. As a specific example, the solvent may include at least one of water and ethylene glycol. If the solvent includes both water and ethylene glycol, the mixing weight ratio of water and ethylene glycol may be, for example, 1:5 or 1:2.
[0048] The temperature (dissolution temperature) at which the recovered BHET is mixed with the solvent may be, for example, 60° C. or higher, 65° C. or higher, 70° C. or higher, or 75° C. or higher, and may be 197° C. or lower, 180° C. or lower, 165° C. or lower, 140° C. or lower, 120° C. or lower, 100° C. or lower, 90° C. or higher. According to a specific embodiment The mixing temperature can be from 60°C to 120° C. Within the above preferred temperature range, it is beneficial to maintain the quality of the recovered BHET solution during storage and to improve the performance of the polyester resin prepared therefrom.
[0049] In the step of preparing the recovered BHET solution, the solvent may be further added or evaporated after mixing to adjust the concentration to a desired concentration.
[0050] Thereafter, the recovered solution of bis(2-hydroxyethyl)terephthalate is stored at a temperature of 120°C or lower. Within the above temperature range, it is beneficial to maintain the quality of the recovered BHET solution during storage and to improve the performance of the polyester resin prepared therefrom. For example, the storage temperature of the recovered BHET solution may be 120°C or lower, 115°C or lower, 110°C or lower, 105°C or lower, 100°C or lower, 95°C or lower, or 90°C or lower, and may be 20°C or higher, 25°C or higher, 40°C or higher, 60°C or higher, 70°C or higher, or 80°C or higher. According to one embodiment, the storage temperature of the recovered BHET solution may be 60°C to 120°C.
[0051] As an example, the storage temperature of the recovered BHET solution can be the same as the temperature (dissolution temperature) at which the recovered BHET solution was prepared. As a specific example, the recovered BHET solution can be prepared at a temperature of 60° C. to 120° C. and stored while maintaining this temperature.
[0052] The storage pressure of the recovered BHET solution may be, for example, 5 kgf / cm 2 or less, 3kgf / cm 2 or less, 2kgf / cm 2 or less, 1.5kgf / cm 2 or less or 1kgf / cm 2 or less, and can be 0.1kgf / cm 2 or greater, 0.3kgf / cm 2 or greater, 0.5kgf / cm 2 or greater or 1kgf / cm 2 As a specific example, the storage pressure of the recovered BHET solution can be 2 kgf / cm 2The preferred pressure range is conducive to maintaining the quality of the recovered BHET solution during storage and improving the performance of the polyester resin prepared therefrom.
[0053] The storage period of the recovered BHET solution can be, for example, 30 days or less, 20 days or less, 15 days or less, 7 days or less, or 5 days or less, and can be 1 hour or more, 6 hours or more, 12 hours or more, or 1 day or more, 2 days or more, or 3 days or more. As a specific example, the storage period of the recovered BHET solution can be 7 days or less. Within the above time range, it is beneficial to maintain the quality of the recovered BHET solution during storage and improve the performance of the polyester resin prepared therefrom.
[0054] According to the method of the present invention, during the storage of the recovered BHET solution, the yellowness index is maintained at According to one embodiment, when the recovered BHET solution is stored, the YID index defined below is maintained at 2 or less.
[0055] YID index = (YID - YID [Day 0]) / YID [Day 0]
[0056] Here, YID[day 0] is the yellowness index of the bis(2-hydroxyethyl)terephthalate solution recovered 30 minutes after the preparation in step (1), and YID is the yellowness index of the bis(2-hydroxyethyl)terephthalate solution recovered after the storage in step (2).
[0057] For example, the YID index may be 2 or less, 1.5 or less, 1 or less, 0.7 or less, 0.5 or less, or 0.3 or less. As a specific example, the YID index may be 0 to 2, 0 to 1.5, 0 to 1, or 0 to 0.5.
[0058] According to the present invention, even if the recovered BHET solution is put into polymerization reaction after it is prepared and stored for a certain period of time, the color quality of the final polyester resin obtained therefrom is hardly deteriorated. According to one embodiment, in the method of storing the recovered bis(2-hydroxyethyl)terephthalate, the color change index according to the following equation is 3 or less.
[0059] Color change index = Col L-b [Day 0] – Col L-b
[0060] Here, Col L-b [Day 0] is a value obtained by subtracting the b value from the L value in the Hunter Lab color space of the first polyester resin injection-molded product, which is prepared by using the recycled bis(2-hydroxyethyl)terephthalate itself without mixing it with a solvent and storing it.L-b is a value obtained by subtracting the b value from the L value in the Hunter Lab color space of the second polyester resin injection molded product, the second polyester resin injection molded product being prepared by using the recycled bis(2-hydroxyethyl)terephthalate after mixing with a solvent and storing in steps (1) and (2). The first and second polyester resin injection molded products having a thickness of 6 mm were prepared under the same polymerization and injection molding conditions except for each bis(2-hydroxyethyl)terephthalate used.
[0061] For example, the color change index may be 3 or less, 2.5 or less, 2 or less, 1.5 or less, 1 or less, 0.5 or less, or 0.3 or less. As a specific example, the color change index may be 0 to 3, 0 to 2, 0 to 1.5, or 0 to 1.
[0062] Furthermore, according to the present invention, during the storage of the recovered BHET solution, the recovered BHET Purity maintained at a certain According to one embodiment, the recovered bis(2-hydroxyethyl) The purity of terephthalate may be 60% or more, and the purity variation according to the following equation may be 20% or less.
[0063] Purity change = rBHET purity [day 0] - rBHET purity
[0064] Here, the rBHET purity [Day 0] refers to the purity of the bis(2-hydroxyethyl)terephthalate recovered in step (1) before mixing with the solvent. The rBHET purity is the purity of the bis(2-hydroxyethyl)terephthalate recovered by evaporating the solvent in the solution after storage in step (2).
[0065] For example, the change in purity can be 20% or less, 15% or less, 10% or less, 5% or less, 3% or less, or 1% or less. Specifically, the change in purity can be 0 to 3, 0 to 2, 0 to 1.5, or 0 to 1.
[0066] Method for preparing polyester resin
[0067] The solution of the recovered bis(2-hydroxyethyl)terephthalate prepared and stored by the above method is used to polymerize a polyester resin.
[0068] That is, the method for preparing a polyester resin according to the present invention includes polymerizing a polyester resin using the above-mentioned stored recycled bis(2-hydroxyethyl)terephthalate (BHET).
[0069] As an example, the solution of recovered bis(2-hydroxyethyl)terephthalate can be directly put into the polymerization reaction of polyester, which may be advantageous in terms of uniform supply of raw materials and reaction efficiency. In particular, when it is added to the polymerization reaction as a solution, the recovered BHET can be continuously introduced, thereby enabling a continuous process of uniform polymerization reaction.
[0070] As another example, the solvent in the recovered bis(2-hydroxyethyl)terephthalate solution may be evaporated to obtain solid-phase recovered bis(2-hydroxyethyl)terephthalate, which is then fed into the polymerization reaction of the polyester resin. In this case, it is advantageous in that the existing method and apparatus for introducing solid-phase recovered BHET can be used as is by storing it as a thermally stable solution, then evaporating the solvent and feeding it into the polymerization reaction.
[0071] In the polymerization, an esterification reaction (first polymerization reaction step) and a polycondensation reaction (second polymerization reaction step) may be performed in sequence.
[0072] In addition to the recovered bis(2-hydroxyethyl)terephthalate, the Dicarboxylic acid or Its derivatives and / or ethylene glycol are used to prepare the polyester resin of the present invention. The lipids can be prepared into copolymers by further adding other diacids (such as dicarboxylic acids) and / or other diols (such as diols) as comonomers.
[0073] For example, at least one monomer selected from the group consisting of (a) a dicarboxylic acid (such as terephthalic acid or a derivative thereof), (b) ethylene glycol or diethylene glycol, and (c) another diol component may be further added as a comonomer to the esterification reaction.
[0074] The dicarboxylic acid may include at least one selected from terephthalic acid and isophthalic acid.
[0075] The diol component added as a comonomer may include at least one selected from the group consisting of cyclohexanedimethanol, cyclohexanedimethanol derivatives and isosorbide. The cyclohexanedimethanol derivative may be 4-(hydroxymethyl)cyclohexylmethyl-4-(hydroxymethyl)cyclohexanecarboxylate or 4-(4-(hydroxymethyl)cyclohexylmethoxymethyl)cyclohexylmethanol.
[0076] In addition, the diol component added as a comonomer may further include 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propylene glycol, 2-methylene-1,3-propylene glycol, 2-ethyl-1,3-propylene glycol, 2-isopropyl-1,3-propylene glycol, 2,2-dimethyl-1,3-propylene glycol, 1,4-butylene glycol, 2,3-butylene glycol, 3-methyl-1,5-pentanediol, 3-methyl-2,4-pentanediol, 1,6-hexanediol, 1,2-cyclohexanediol, and 1,4-cyclohexanediol.
[0077] The esterification reaction can be carried out in the presence of an esterification catalyst. For example, a zinc-based compound can be used. Specific examples of zinc-based catalysts include zinc acetate, zinc acetate hydrate, zinc chloride, zinc sulfate, zinc sulfide, zinc carbonate, zinc citrate, zinc gluconate, or mixtures thereof.
[0078] The esterification reaction can be carried out, for example, at 0 kgf / cm 2 Up to 10.0kgf / cm 2 The esterification reaction conditions can be appropriately adjusted according to the specific characteristics of the polyester produced, the proportion of each component or the process conditions. Specifically, the pressure in the esterification reaction can be 0 kg / cm 2 Up to 5.0kg / cm 2 , more specifically, 0.1 kg / cm 2 Up to 3.0kg / cm 2 In addition, the temperature of the esterification reaction may be 200°C to 270°C, and more specifically, 240°C to 260°C.
[0079] The esterification reaction can be carried out in an intermittent or continuous manner. In addition, the recovered BHET, dicarboxylic acid component and diol component as raw materials can be introduced into the reactor separately, or two or more raw materials can be introduced in a mixed state. They can be introduced in the form of solid, liquid or slurry. As an example, the dicarboxylic acid component, diol component and recovered BHET can be added individually or in combination, and can be It can be mixed with the previously prepared terephthalic acid oligomer. The polymer can be obtained by, for example, Phthalic acid is prepared by reacting diols such as ethylene glycol, cyclohexanedimethanol and isosorbide. As another example, they can be introduced in the form of a slurry where the dicarboxylic acid component and recovered BHET are mixed with the diol component.
[0080] More specifically, a diol component (such as isosorbide) that is solid at room temperature can be dissolved in water or ethylene glycol, and then mixed with a dicarboxylic acid component (such as terephthalic acid) to prepare a slurry. Alternatively, isosorbide can be melted at 60°C or higher, and then mixed with a dicarboxylic acid component (such as terephthalic acid) and other diol components to prepare a slurry. In addition, water can be added to the mixed slurry to help increase the fluidity of the slurry. In addition, in a continuous type, a pump, etc. can be used to continuously feed a liquid raw material (for example, a solution of BHET recovered) into a reactor. The raw material feed rate per hour can be determined by dividing the total amount of feed by the time to reach a target output per day (for example, 50 tons / day).
[0081] The solution mixture of the recovered bis(2-hydroxyethyl)terephthalate and other additive components is placed in an esterification reactor for a certain period of time (e.g., 1 to 24 hours or 4 to 10 hours) and then transferred to a polycondensation reactor. The polycondensation reaction can produce a polyester resin with a relatively low molecular weight by melt polymerization. In addition, a polyester resin with a relatively high molecular weight can also be produced by solid state polymerization after melt polymerization.
[0082] The temperature in the polycondensation reaction may be 150°C to 300°C, specifically, 200°C to 290°C, more specifically, 260°C to 280°C. In addition, the pressure in the polycondensation reaction may be 0.01 mmHg to 600 mmHg, specifically, 0.05 mmHg to 200 mmHg, more specifically, 0.1 mmHg to 100 mmHg. Since the polycondensation reaction adopts reduced pressure conditions, the by-product glycol of the polycondensation reaction can be removed from the system. If the pressure in the polycondensation reaction exceeds the range of 0.01 mmHg to 400 mmHg, the removal of the by-product may be insufficient. In addition, if the polycondensation reaction temperature is lower than 150°C, the glycol as a reaction by-product cannot be effectively removed from the system; therefore, the intrinsic viscosity of the final reaction product is low, resulting in a decrease in the physical properties of the final polyester resin. If the temperature of the polycondensation reaction exceeds 300°C, the possibility of yellowing of the final polyester resin increases. Additionally, the polycondensation reaction may be carried out for a necessary time, such as an average residence time of 1 hour to 24 hours, until the intrinsic viscosity of the final reaction product reaches an appropriate level.
[0083] In addition, the polycondensation reaction can be carried out in the presence of a polycondensation catalyst. The polycondensation catalyst can be, for example, a titanium-based compound, a germanium-based compound, an antimony-based compound, an aluminum-based compound, a tin-based compound, or a mixture thereof. Examples of titanium compounds include tetraethyl titanate, acetyl tripropyl titanate, tetrapropyl titanate, tetrabutyl titanate, 2-ethylhexyl titanate, octanediol titanate, triethanolamine titanate, acetylacetone titanate, ethyl acetoacetate titanate, isostearyl titanate, titanium dioxide, etc. Examples of germanium-based compounds include germanium dioxide, germanium tetrachloride, ethylene glycol germanium oxide, germanium acetate, or a mixture thereof. Preferably, germanium dioxide can be used. Crystalline germanium dioxide and amorphous germanium dioxide can be used, and germanium dioxide soluble in ethylene glycol can also be used. The amount of the polycondensation catalyst can be such that the amount of the titanium element is about 1ppm to 100ppm relative to the weight of the polyester resin, more preferably about 1ppm to 50ppm.
[0084] In addition to the polycondensation catalyst, it is also possible to use a stabilizer, a colorant, a crystallizing agent, an antioxidant, a branching agent, etc. The timing of adding these additives is not particularly limited, and they may be added at any time in the preparation step of the polyester resin.
[0085] As a stabilizer, phosphorus-based compounds such as phosphoric acid, trimethyl phosphate, triethyl phosphate and triethyl phosphonoacetate can generally be used. Based on the amount of the element, the addition amount can be 10ppm to 200ppm relative to the weight of the polyester resin. In addition, common colorants such as cobalt acetate and cobalt propionate can also be used as colorants to increase the color of the polyester resin. Based on the amount of the cobalt element, the addition amount can be 10ppm to 200ppm relative to the weight of the polyester resin. If necessary, anthraquinone compounds, purple cyclic ketone compounds, azo compounds, methine compounds, etc. can be used as organic colorants. Commercially available toners can be used, such as Polysynthren Blue RLS from Clarient or Solvaperm Red BB from Clarient. Based on the weight of the polyester resin, the addition amount of the organic compound colorant can be adjusted to 0ppm to 50ppm. Crystallization nucleating agents, ultraviolet absorbers, polyolefin resins, polyamide resins, etc. can be used as crystallizing agents. Hindered phenol-based antioxidants, phosphite-based antioxidants, thioether-based antioxidants or mixtures thereof may be used as antioxidants. Conventional branching agents having three or more functional groups, such as trimellitic anhydride, trimethylolpropane, trimellitic acid or mixtures thereof, may be exemplified as branching agents.
[0086] Composition and properties of polyester resin
[0087] The polyester resin of the present invention is a polyester resin regenerated by chemical recovery of waste polyester.
[0088] The polyester resin according to an embodiment of the present invention includes the recycled bis(2-hydroxyethyl)terephthalate stored by the above method.
[0089] Specifically, since the polyester resin of the present invention is polymerized using recycled BHET, it includes a repeating unit derived from the recycled BHET in a polymer chain.
[0090] The content of BHET recovered in the polyester resin of the present invention may be 1 wt % or more, 5 wt % or more, 10 wt % or more, 30 wt % or more, 50 wt % or more, 70 wt % or more, or 90 wt % or more. In addition, the content of BHET recovered may be 100 wt % or less, 99 wt % or less, 80 wt % or less, 60 wt % or less, 40 wt % or less, or 20 wt % or less.
[0091] As an example, the amount of recycled bis(2-hydroxyethyl)terephthalate used may be 10 wt % to 99 wt % based on the weight of the polyester resin.
[0092] Meanwhile, since bis(2-hydroxyethyl)terephthalate has a structure in which two ethylene glycols and one terephthalic acid are bonded, the polyester resin of the present invention may substantially include repeating units derived from ethylene glycol and terephthalic acid.
[0093] As described above, the monomers constituting the polyester resin of the present invention include a diacid component and a diol component. In addition, the polyester resin of the present invention may further include an additional diacid component and an additional diol component for polyester polymerization.
[0094] In the polyester resin of the present invention, the diacid component may be a dicarboxylic acid or a derivative thereof, and the diol component may be a diol.
[0095] In particular, the dicarboxylic acid includes terephthalic acid, and the physical properties of the polyester resin, such as heat resistance, chemical resistance and weather resistance, can be enhanced by terephthalic acid. For example, based on the mole number of all dicarboxylic acids, the amount of terephthalic acid can be 5 mol% to 100 mol%. In addition, the terephthalic acid component can be formed by alkyl terephthalate, such as dimethyl terephthalate.
[0096] In addition, the diol includes ethylene glycol or diethylene glycol, and ethylene glycol or diethylene glycol can help improve the transparency and impact resistance of the polyester resin. For example, based on the mole number of all diols, the amount of ethylene glycol and / or diethylene glycol can be 5 mol% to 100 mol%.
[0097] According to one embodiment, the polyester resin of the present invention may be a polyester resin comprising two or more dicarboxylic acid groups. and / or copolymer resins of two or more diol components.
[0098] Specifically, the dicarboxylic acid component may include an aromatic dicarboxylic acid component, an aliphatic dicarboxylic acid component or a mixture thereof in addition to terephthalic acid. The dicarboxylic acid in addition to terephthalic acid may be used in an amount of 1 mol% to 30 mol% based on the weight of all dicarboxylic acid components.
[0099] The aromatic dicarboxylic acid component may be an aromatic dicarboxylic acid having 8 to 20 carbon atoms, preferably an aromatic dicarboxylic acid having 8 to 14 carbon atoms, or a mixture thereof. Examples of aromatic dicarboxylic acids include isophthalic acid, naphthalene dicarboxylic acid (such as 2,6-naphthalene dicarboxylic acid), diphenyl dicarboxylic acid, 4,4'-stilbene dicarboxylic acid, 2,5-furan dicarboxylic acid, 2,5-thiophene dicarboxylic acid, etc., but are not limited thereto.
[0100] The aliphatic dicarboxylic acid component may be an aliphatic dicarboxylic acid having 4 to 20 carbon atoms, preferably 4 to 12 carbon atoms, or a mixture thereof. Examples of aliphatic dicarboxylic acids include linear, branched or cyclic aliphatic dicarboxylic acid components (such as cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid and 1,3-cyclohexanedicarboxylic acid), phthalic acid, sebacic acid, succinic acid, isodecylsuccinic acid, maleic acid, fumaric acid, adipic acid, glutaric acid, azelaic acid, etc., but are not limited thereto.
[0101] In addition, the diol component may further include a comonomer other than ethylene glycol or diethylene glycol. For example, the comonomer may include at least one selected from the group consisting of cyclohexanedimethanol, cyclohexanedimethanol derivatives, and isosorbide.
[0102] Cyclohexanedimethanol (e.g., 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, and 1,4-cyclohexanedimethanol) can contribute to improving the transparency and impact resistance of the produced polyester resin. For example, based on the mole number of all diols, the amount of cyclohexanedimethanol used is 5 mol% to 90 mol%. The cyclohexanedimethanol derivative can be 4-(hydroxymethyl)cyclohexylmethyl-4-(hydroxymethyl)cyclohexanecarboxylate or 4-(4-(hydroxymethyl)cyclohexylmethoxymethyl)cyclohexylmethanol. Based on the mole number of all diols, the amount of the cyclohexanedimethanol derivative can be 0.1 mol% to 25 mol%.
[0103] Isosorbide can improve the processing properties of the final polyester resin. Although the diol components in cyclohexanedimethanol and ethylene glycol enhance the transparency and impact resistance of the polyester resin, for the sake of processing performance, the shear fluidization characteristics should be improved and the crystallization rate should be delayed; however, it is difficult to achieve this effect using cyclohexanedimethanol and ethylene glycol alone. Therefore, if isosorbide is used as the diol component, To improve shear fluidization characteristics and slow down crystallization speed while maintaining Brightness and impact resistance, from Preferably, isosorbide can be used in an amount of 0.1 mol % to 50 mol % based on the moles of all diols.
[0104] As a specific example, the polyester resin includes a diacid component and a diol component, wherein the diacid component may include at least one selected from the group consisting of terephthalic acid, isophthalic acid, dimethyl isophthalate, phthalic acid, dimethyl phthalate, phthalic anhydride, 2,6-naphthalene dicarboxylic acid, dimethyl 2,6-naphthalene dicarboxylate, diphthalic acid, 1,4-cyclohexane dicarboxylic acid, 1,3-cyclohexane dicarboxylic acid, dimethyl 1,4-cyclohexane dicarboxylate, dimethyl 1,3-cyclohexane dicarboxylate, sebacic acid, succinic acid, isodecyl succinic acid, maleic acid, maleic anhydride, fumaric acid, adipic acid, glutaric acid and azelaic acid, and the diol component may include at least one selected from the group consisting of isophthalic acid, At least one of the group consisting of sorbitol, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propylene glycol, 2-methylene-1,3-propylene glycol, 2-ethyl-1,3-propylene glycol, 2-isopropyl-1,3-propylene glycol, 2,2-dimethyl-1,3-propylene glycol, 1,4-butylene glycol, 2,3-butylene glycol, 3-methyl-1,5-pentanediol, 3-methyl-2,4-pentanediol, 1,6-hexanediol, 1,2-cyclohexanediol, 1,4-cyclohexanediol, diethylene glycol, 4-(hydroxymethyl)cyclohexylmethyl-4-(hydroxymethyl)cyclohexanecarboxylate and 4-(4-(hydroxymethyl)cyclohexylmethoxymethyl)cyclohexylmethanol.
[0105] According to one embodiment, in addition to bis(2-hydroxyethyl)terephthalate, the polyester resin may further include at least one monomer selected from the group consisting of: (a) dicarboxylic acid or a derivative thereof, (b) ethylene glycol or diethylene glycol, and (c) a diol-based comonomer. The dicarboxylic acid may include at least one selected from terephthalic acid and isophthalic acid. In addition, the diol-based comonomer may include at least one selected from the group consisting of cyclohexanedimethanol, cyclohexanedimethanol derivatives and isosorbide. The cyclohexanedimethanol derivative may be 4-(hydroxymethyl)cyclohexylmethyl-4-(hydroxymethyl)cyclohexanecarboxylate or 4-(4-(hydroxymethyl)cyclohexylmethoxymethyl)cyclohexylmethanol. The diol-based comonomer may further include 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propylene glycol, 2-methylene-1,3-propylene glycol, 2-ethyl-1,3-propylene glycol, 2-isopropyl-1,3-propylene glycol, 2,2-dimethyl-1,3-propylene glycol, 1,4-butanediol, 2,3-butanediol, 3-methyl-1,5-pentanediol, 3-methyl-2,4-pentanediol, 1,6-hexanediol, 1,2-cyclohexanediol and 1,4-cyclohexanediol.
[0106] The polyester resin may also contain a catalyst which has been used in the polymerization reaction to make Polyester Tree For example, the polyester resin may contain at least one selected from metal oxides and acetates.Catalyst. The metal contained in the catalyst may be selected from the group consisting of antimony (Sb), titanium (Ti), germanium (Ge), manganese (Mn), cobalt (Co), tin (Sn), and calcium (Ca).
[0107] When measuring the Hunter Lab color space, the value obtained by subtracting the b value from the L value of the polyester resin may be 85 or more. For example, the Lb value may be 85 or more, 86 or more, 87 or more, 88 or more, 89 or more, 90 or more, or 91 or more. In addition, the upper limit of the Lb value is not particularly limited. However, it may be, for example, 100 or less, 99 or less, 98 or less, 97 or less, or 95 or less. The measurement of the Hunter Lab color space can be performed by making a sample with a thickness of 6 mm with polyester resin.
[0108] The intrinsic viscosity of the polyester resin according to the present invention at 35°C may be 0.5 dl / g or more, 0.6 dl / g or more, or 0.7 dl / g or more, and may be 1.2 dl / g or less, 1.1 dl / g or less, 1.0 dl / g or less, or 0.9 dl / g or less. For example, the intrinsic viscosity of the polyester resin at 35°C may be 0.5 dl / g to 1.2 dl / g. Specifically, the intrinsic viscosity of the polyester resin at 35°C may be 0.5 dl / g to 0.9 dl / g.
[0109] The polyester resin according to the present invention can be used as a material for beverage filling containers, packaging films, audio-visual films, etc., by virtue of its excellent color, mechanical strength, heat resistance, transparency, and gas barrier properties. In addition, polyester sheets or plates prepared from the polyester resin according to the present invention have good transparency and excellent mechanical strength, so they can be used as raw materials for boxes, boxes, partitions, shelves, panels, packaging materials, building materials, interior and exterior materials, etc. In addition, the polyester resin according to the present invention can be used as an industrial material such as medical fibers and tire cords.
[0110] Therefore, the present invention provides a product comprising a polyester resin. As an example, the product can be a film, a sheet or a profile. Specific examples of films include heat shrinkable films and blown films. Profiles refer to plastic products that are continuously extruded, excluding sheets and films. It can be manufactured by a general extrusion molding method and can have, for example, a tubular or channel shape. DETAILED DESCRIPTION
[0111] Mode for the Invention
[0112] Below, we will describe the present invention in more detail in conjunction with the embodiments. These examples are for illustrative purposes only, and the present invention is not limited thereto.
[0113] Preparation of recovered bis(2-hydroxyethyl)terephthalate
[0114] Recovered BHET (rBHET) of various purities were prepared by depolymerization of waste polyester resins purchased by a known method or commercially. The following table shows the peak area fraction (%) of BHET in the HPLC results of each recovered BHET (rBHET) measured using HPLC, that is, the purity.
[0115] [Table 1]
[0116]
[0117] Example 1
[0118] Step A: Preparation and storage of r-BHET solution
[0119] At 120°C, rBHET#1 prepared as recovered bis(2-hydroxyethyl)terephthalate as above was dissolved in ethylene glycol (EG) as a solvent to obtain a solution having a concentration of 25 wt%. The recovered bis(2-hydroxyethyl)terephthalate solution was stirred at the same temperature (120°C) and 1 kgf / cm 2 The mixture was stored under pressure for 7 days and used as is in the next step.
[0120] Step B: Polymerization of polyester resin
[0121] The esterification reactor was charged with the recovered bis(2-hydroxyethyl)terephthalate solution obtained in the previous step (weight of rBHET#1: 19,051.9 kg), terephthalic acid (TPA, 29,052.9 kg), ethylene glycol (e.g., 6,665.7 kg), 1,4-cyclohexanedimethanol (CHDM, 4,320.4 kg), isosorbide (ISB, 1,460.1 kg), diethylene glycol (DEG, 265.0 kg), Ge catalyst (64.0 kg), phosphoric acid (50.0 kg), blue toner (0.050 kg) and red toner (0.025 kg). Subsequently, nitrogen was injected into the esterification reactor so that the pressure inside the reactor was 2.0 kgf / cm higher than the normal pressure (absolute pressure: 2,231.1 mmHg). 2. Then, the temperature of the esterification reactor is raised to 220°C within 90 minutes, and maintained at 220°C for 2 hours, and then the temperature is raised to 260°C again within 2 hours. The mixture in the esterification reactor is stored at 260°C for about 7 hours, and then transferred to the polycondensation reactor, and the by-products formed during the reaction are discharged through the tower and the condenser. Then, the pressure of the polycondensation reactor is reduced from normal pressure to 5 Torr (absolute pressure: 5 mmHg) in 30 minutes. At the same time, the temperature of the polycondensation reactor is raised to 280°C in 1 hour, and then the polycondensation reaction is carried out while the pressure of the polycondensation reactor is maintained at 1 Torr (absolute pressure: 1 mmHg) or less. At the beginning of the polycondensation reaction, the stirring speed can be set higher. As the polycondensation reaction proceeds, when the stirring power is weakened due to the increase in the viscosity of the reactants or the temperature of the reactants rises to above the set temperature, the stirring speed can be appropriately adjusted accordingly. The polycondensation reaction is carried out until the intrinsic viscosity (IV) of the mixture (melt) in the reactor reaches 0.70 dl / g.
[0122] When the intrinsic viscosity of the mixture in the reactor reaches a desired level, the mixture is then discharged to the outside of the reactor to form pellets, the pellets are solidified with a cooling liquid, and then granulated to have an average weight of about 12 to 14 mg. The pellets are placed at 150° C. for 1 hour to crystallize, and then added to a solid phase polymerization reactor. While nitrogen flows at a rate of 50 liters / minute, the temperature of the reactor is raised from room temperature to 190° C. at a rate of 40° C. / hour. While maintaining this state, solid phase polymerization is performed until the intrinsic viscosity (IV) of the pellets in the reactor reaches 1.20 dl / g, thereby obtaining about 50 tons of a polyester resin (copolymer).
[0123] Example 2
[0124] The same steps as in Example 1 were repeated to obtain about 50 tons of a polyester resin (copolymer), except that in step A, r-BHET#2 was used as the recycled bis(2-hydroxyethyl)terephthalate, water was used as the solvent at a concentration of 25% by weight, the dissolution and storage temperature was 100° C., and the storage pressure was 2 kgf / cm 2; and in step B, the reactor is charged with the recovered bis(2-hydroxyethyl)terephthalate solution (weight of rBHET#2: 64,677.1 kg), ethylene glycol (EG, 263.1 kg), 1,4-cyclohexanedimethanol (CHDM, 1,833.4 kg), isosorbide (ISB, 495.7 kg), diethylene glycol (DEG, 539.8 kg), Ge catalyst (32.0 kg), blue colorant (0.150 kg) and red colorant (0.075 kg), and the condensation reaction is carried out until the intrinsic viscosity (IV) of the mixture (molten material) in the reactor reaches 0.60 dl / g, and solid-state polymerization is carried out until the intrinsic viscosity (IV) of the particles in the reactor reaches 0.85 dl / g.
[0125] Example 3
[0126] The same steps as in Example 1 were repeated to obtain about 50 tons of polyester resin (copolymer), except that in step A, r-BHET#3 was used as the recovered bis(2-hydroxyethyl)terephthalate, water was used as the solvent, the concentration was 70% by weight, the dissolution and storage temperature was 90° C., and the storage pressure was 2.5 t / s. Force is 1kgf / cm 2 ; and, in step B, adding Add the recovered bis(2-hydroxyethyl) Phthalate solution (weight of rBHET#3: 48,636.6 kg), terephthalic acid (TPA, 10,595.4 kg), ethylene glycol (EG, 474.9 kg), 1,4-cyclohexanedimethanol (CHDM, 735.3 kg), diethylene glycol (DEG, 1,353.1 kg), Ge catalyst (32.0 kg), Ti catalyst (4.5 kg), phosphoric acid (5.0 kg), blue colorant (0.200 kg) and red colorant (0.050 kg) were reacted to carry out polycondensation until the intrinsic viscosity (IV) of the mixture (molten material) in the reactor reached 0.70 dl / g, and solid phase polymerization was no longer carried out.
[0127] Example 4
[0128] The same steps as in Example 1 were repeated to obtain about 50 tons of polyester resin (copolymer), except that in step A, r-BHET#4 was used as recycled bis(2-hydroxyethyl) terephthalate, ethylene glycol (EG) was used as solvent, the concentration was 90% by weight, the dissolution and storage temperature was 120° C., and the storage pressure was 1 kgf / cm 2; And, in step B, the reactor was charged with a recovered bis(2-hydroxyethyl)terephthalate solution (weight of rBHET#4: 6,392.2 kg), terephthalic acid (TPA, 37,598.1 kg), ethylene glycol (EG, 13,106.5 kg), 1,4-cyclohexanedimethanol (CHDM, 2,174.4 kg), diethylene glycol (DEG, 1,333.8 kg), Ti catalyst (2.2 kg) and phosphoric acid (10.0 kg). The polycondensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (molten material) in the reactor reached 0.60 dl / g, and the solid state polymerization was carried out until the intrinsic viscosity (IV) of the pellets in the reactor reached 1.00 dl / g.
[0129] Example 5
[0130] The same steps as in Example 1 were repeated to obtain about 50 tons of polyester resin (copolymer), except that r-BHET#5 was used as the recovered bis(2-hydroxyethyl)terephthalate in step A, water was used as the solvent at a concentration of 95% by weight, the dissolution and storage temperature was 100° C., and the storage pressure was 1.5 kgf / cm 2 ; and, in step B, the recovered bis(2-hydroxyethyl)terephthalate solution (weight of rBHET#5: 49,166.5 kg), terephthalic acid (TPA, 5,670.4 kg), ethylene glycol (EG, 706.0 kg), 1,4-cyclohexanedimethanol (CHDM, 10,493.7 kg), a CHDM derivative (composed of 4-(hydroxymethyl)cyclohexylmethyl-4-(hydroxymethyl)cyclohexanecarboxylate and 4-(4-(hydroxymethyl)cyclohexylmethoxymethyl)cyclohexylmethanol in a molar ratio of 1:3, 997.4 kg), Ge catalyst (64.0 kg), Ti catalyst (4.5 kg), phosphoric acid (5.0 kg), cobalt acetate (6.3 kg), blue toner (0.030 kg) and red toner (0.010 kg) were added to the reactor to carry out a polycondensation reaction until the mixture (molten material) in the reactor reached a specific temperature of 100 °C. The viscosity (IV) reached 0.78 dl / g and no solid state polymerization was performed. combine.
[0131] Example 6
[0132] The same steps as in Example 1 were repeated to obtain about 50 tons of a polyester resin (copolymer), except that in step A, r-BHET#6 was used as the recycled bis(2-hydroxyethyl)terephthalate, ethylene glycol (EG) was used as the solvent, the concentration was 85% by weight, the dissolution and storage temperature was 120° C., and the storage pressure was 1 kgf / cm 2; and, in step B, the recovered bis(2-hydroxyethyl)terephthalate solution (weight of rBHET#6: 13,403.4 kg), terephthalic acid (TPA, 26,279.1 kg), 1,4-cyclohexanedimethanol (CHDM, 19,756.8 kg), isosorbide (ISB, 6,163.5 kg), diethylene glycol (DEG, 2,237.4 kg), Ge catalyst (320.2 kg), phosphoric acid (1.0 kg), blue toner (0.150 kg) and red toner (0.050 kg) were added to the reactor to carry out a polycondensation reaction until the intrinsic viscosity (IV) of the mixture (molten material) in the reactor reached 0.70 dl / g, and solid-state polymerization was no longer carried out.
[0133] Example 7
[0134] The same steps as in Example 1 were repeated to obtain about 50 tons of polyester resin (copolymer), except that in step A, r-BHET#7 was used as the recycled bis(2-hydroxyethyl)terephthalate, ethylene glycol (EG) was used as the solvent, the concentration was 50% by weight, the dissolution and storage temperature was 120° C., and the storage pressure was 1 kgf / cm 2 ; and, in step B, the recovered bis(2-hydroxyethyl)terephthalate solution (weight of rBHET#7: 31,552.1 kg), terephthalic acid (TPA, 16,871.4 kg), isophthalic acid (IPA, 20,620.7 kg), ethylene glycol (EG, 2,660.6 kg), 1,4-cyclohexanedimethanol (CHDM, 10,082.2 kg), diethylene glycol (DEG, 2,394.1 kg), Ti catalyst (0.9 kg), phosphoric acid (10.0 kg) and cobalt acetate (13.7 kg) were added into the reactor to carry out a polycondensation reaction until the intrinsic viscosity (IV) of the mixture (molten material) in the reactor reached 0.82 dl / g, and solid-state polymerization was no longer carried out.
[0135] Comparative Example 1
[0136] The same steps as in Example 1 were repeated to obtain about 50 tons of polyester resin (copolymer), except that in step A, r-BHET#5-1 was used as the recovered bis(2-hydroxyethyl)terephthalate, which was not mixed with a solvent and heated at 160°C and 1.5 kgf / cm 2 and stored for 7 days; and, in step B, the recovered bis(2-hydroxyethyl)terephthalate (weight of rBHET#5-1: 49,166.5 kg), terephthalic acid (TPA, 5,670.4 kg), ethylene glycol (EG, 706.0 kg), 1,4-cyclohexane Alkanedimethanol (CHDM, 10, 493.7 kg), CHDM derivatives (comprising 4-(hydroxymethyl) base) The invention relates to a novel catalyst comprising cyclohexylmethyl-4-(hydroxymethyl)cyclohexanecarboxylate and 4-(4-(hydroxymethyl)cyclohexylmethoxymethyl)cyclohexylmethanol, 997.4kg), a Ge catalyst (64.0kg), a titanium catalyst (4.5kg), phosphoric acid (5.0kg), cobalt acetate (6.3kg), a blue toner (0.030kg) and a red toner (0.010kg), and a condensation reaction is carried out until the intrinsic viscosity (IV) of the mixture (molten material) in the reactor reaches 0.78dl / g, and solid-state polymerization is no longer carried out.
[0137] Comparative Example 2
[0138] The same steps as in Example 1 were repeated to obtain about 50 tons of polyester resin (copolymer), except that in step A, r-BHET#1-1 was used as the recovered bis(2-hydroxyethyl)terephthalate, ethylene glycol (EG) was used as the solvent, the concentration was 98 wt %, the dissolution and storage temperature was 180° C., and the storage pressure was 1.8 kgf / cm 2 ; and, in step B, the recovered bis(2-hydroxyethyl)terephthalate solution (weight of rBHET#1-1: 19,051.9 kg), terephthalic acid (TPA, 29,052.9 kg), ethylene glycol (EG, 6,665.7 kg), 1,4-cyclohexanedimethanol (CHDM, 4,320.4 kg), isosorbide (ISB, 1,460.1 kg), diethylene glycol (DEG, 265.0 kg), Ge catalyst (64.0 kg), phosphoric acid (50.0 kg), blue toner (0.050 kg) and red toner (0.025 kg) were added to the reactor, and a condensation reaction was carried out until the intrinsic viscosity (IV) of the mixture (molten material) in the reactor reached 0.70 dl / g, and solid state polymerization was carried out until the intrinsic viscosity (IV) of the particles in the reactor reached 1.20 dl / g.
[0139] Comparative Example 3
[0140] The same steps as in Example 1 were repeated to obtain about 50 tons of polyester resin (copolymer), except that in step A, r-BHET#7-1 was used as the recovered bis(2-hydroxyethyl)terephthalate, which was not mixed with a solvent and heated at 120°C, 1 kgf / cm 2and, in step B, a solution of recovered bis(2-hydroxyethyl)terephthalate solution (weight of rBHET#7-1: 31,552.1 kg), terephthalic acid (TPA, 16,871.4 kg), ethylene glycol (EG, 2,660.6 kg), 1,4-cyclohexanedimethanol (CHDM, 10,082.2 kg), diethylene glycol (DEG, 2,394.1 kg), Ti catalyst (0.9 kg), phosphoric acid (10.0 kg) and cobalt acetate (13.7 kg) were added to the reactor to carry out a polycondensation reaction until the intrinsic viscosity (IV) of the mixture (molten material) in the reactor reached 0.78 dl / g, and then no solid phase polymerization was carried out.
[0141] Test Example 1: Evaluation of Recovered BHET Solution
[0142] The recovered BHET solution was evaluated as follows.
[0143] (1)YID
[0144] - Test method: Use Hunter Lab's Color Flex EZ to obtain the transmittance data of the solution at an observer angle of 2° with illuminant D65. Use the color analyzer in the software to calculate the yellow index (YID) value.
[0145] -YID [Day 0] test: The recovered BHET solution (stored for 0 days) was prepared in step A of Examples 1 to 7 and Comparative Examples 1 to 3, and the yellowness index was measured after 30 minutes. In Comparative Examples 1 and 3, in which no solution was prepared, the recovered BHET was dissolved in ethylene glycol (EG) at a concentration of 25 wt % at 120° C., and the yellowness index was measured after 30 minutes.
[0146] - Tests of YID [Day 1] and YID [Day 7]: After the recovered BHET solution was stored for 1 day and 7 days under the storage conditions of step A of Examples 1 to 7 and Comparative Examples 1 to 3, the yellowness index was measured in the same manner as above.
[0147] -YID index is calculated according to the following equation.
[0148] YID index = (YID[Day 7] – YID[Day 0]) / YID[Day 0]
[0149] Here, YID[Day 0] is the yellowness index of the recovered BHET solution at 30 minutes after its preparation, and YID[Day 7] is the yellowness index of the recovered BHET solution after storage for 7 days.
[0150] (2) High performance liquid chromatography (HPLC)
[0151] -Analysis method: About 0.01 g of the recovered BHET sample was diluted in about 20 ml of methanol and analyzed by high performance liquid chromatography (HPLC) (model: Waters e2695, chromatographic column: C18 (4.6×250 mm), 5,0, UV detector: 242 nm, injection volume: 10 sample volumes, eluent (gradient) A: H2O+H3PO4, B: acetonitrile)
[0152] Test of rBHET Purity [Day 0]: The recovered BHET used in Step A of Examples 1-7 and Comparative Examples 1-3, respectively, was analyzed by HPLC before mixing with the solvent to determine the peak area fraction of BHET in the total peak area.
[0153] -rBHET purity [Day 1], rBHET purity [Day 3], rBHET purity [Day 5] and Test of rBHET purity [Day 7]: Each recovered BHET solution was stored for 1, 3, 5 and 7 days under the storage conditions in step A of Examples 1-7 and Comparative Examples 1-3, and then the solvent was evaporated and analyzed by HPLC in the same manner as above. In Comparative Examples 1 and 3, in which the recovered BHET was not mixed with a solvent, the recovered BHET was stored in a solid state and then the yellowness index was measured.
[0154] -The purity change was calculated according to the following equation.
[0155] Purity change = rBHET purity [day 0] – rBHET purity [day 7]
[0156] Here, rBHET purity [day 0] is the purity of the recovered bis(2-hydroxyethyl)terephthalate before mixing with the solvent, and rBHET purity [day 7] is the purity obtained by evaporating the solvent in the solution after the recovered bis(2-hydroxyethyl)terephthalate was stored for 7 days.
[0157] Tables 2 and 3 below show the preparation and storage conditions and test results of the BHET solutions recovered in the Examples and Comparative Examples.
[0158] [Table 2]
[0159]
[0160] [Table 3]
[0161]
[0162] As can be seen from Tables 2 and 3 above, the recovered BHET solutions prepared and stored under the preferred concentration and temperature conditions in Examples 1 to 7 still maintained high purity after 7 days, with a YID index of 2 or less, indicating that polyester resins with good quality can be produced therefrom.
[0163] In contrast, in Comparative Examples 1 to 3, the recovered BHET solutions prepared and stored under conditions other than the preferred concentration and temperature showed a significant decrease in purity after 7 days, with a YID index exceeding 2, indicating that the polyester resin produced therefrom would be of poor quality.
[0164] <Preparation and Evaluation of Polyester Resins>
[0165] The preparation and evaluation procedures of the polyester resins were as follows.
[0166] (0) Preparation of polyester resin
[0167] <Test Group> Each polyester resin was prepared according to the steps of Examples 1 to 7 and Comparative Examples 1 to 3 (ie, a recovered BHET solution was prepared and stored for 7 days, and then a polymerization reaction was performed to prepare a polyester resin).
[0168] <Control Group> The steps of Examples 1 to 7 and Comparative Examples 1 to 3 were performed, but the step of mixing the recovered BHET with a solvent or storing it under specific temperature and pressure conditions (ie, step A) was not performed, and step B was performed to prepare a polyester resin.
[0169] (1) Intrinsic viscosity (IV)
[0170] The polyester resin was dissolved in o-chlorophenol (OCP) at a concentration of 0.12% at 150° C. to obtain a solution, and the intrinsic viscosity was measured using an Ubbelohde viscometer in a constant temperature bath at 35° C. Specifically, the temperature of the viscous tube was maintained at 35° C., and the time required for the solvent to pass between specific internal sections of the viscous tube (flow time) and the time required for the solution to pass were calculated to obtain the specific viscosity, which was used to calculate the intrinsic viscosity.
[0171] In Examples 1 to 7 and Comparative Examples 1 to 3, the intrinsic viscosity (ie, melt IV) of the polyester resin measured after melt polymerization and the intrinsic viscosity (ie, solid IV) measured after solid phase polymerization after melt polymerization are shown in the following table.
[0172] (2) Composition
[0173] Each polyester resin was dissolved in CDCl3 solvent at a concentration of 3 mg / ml, and its molecular weight was obtained at 25°C using a nuclear magnetic resonance device (JEOL, 600 MHz FT-NMR). 1 H-NMR spectrum. Based on the total molar number of residues derived from all diols (EG, DEG, BD, PDO, PTMG, PO3G, EO-PPG, etc.), the contents (mol %) of diethylene glycol (DEG), isosorbide (ISB) and cyclohexanedimethanol (CHDM) residues were calculated by analyzing the above spectrum.
[0174] The composition of the polyester resins was tested on the experimental group (preparation of the recovered BHET solution and storage for 7 days before polymerization) and the control group (direct polymerization using the recovered BHET without mixing with solvent or storage).
[0175] (3) Color
[0176] The chromaticity and brightness of the samples were measured using a Varian Cary 5 UV / Vis / NIR spectrophotometer equipped with a diffuse reflectance accessory. A polyester resin sample with a thickness of 6 mm was prepared by injection molding at 250°C, for which transmittance data was obtained with a light source D65 at an observer angle of 2° and processed using a color analyzer in Grams / 32 software to calculate Hunter Lab values. The value of L value minus b value (Lb) was calculated.
[0177] Color tests were performed on polyester resins of the test group (polymerization after preparation of the recycled BHET solution and storage for 7 days) and the control group (polymerization using the recycled BHET without mixing with solvent or storage).
[0178] The test results are shown in Tables 4 and 5 below.
[0179] [Table 4]
[0180]
[0181] [Table 5]
[0182]
[0183] As can be seen from Tables 4 and 5 above, although the polyester resins of Examples 1 to 7 were prepared from recycled BHET stored for a certain period of time (7 days), the components (DEG, ISB and CHDM contents) did not change compared to the polyester prepared from recycled BHET that was not stored for a certain period of time (storage for 0 days). In particular, the color change index (change in Hunter Lb value) was very small, proving that there was almost no quality deterioration in color.
[0184] In contrast, although the components of the polyester resins of Comparative Examples 1 to 3 were not changed, the color change index (change in Hunter Lb value) exceeded 3, demonstrating that the color quality was significantly deteriorated.
Claims
1. A method for storing recovered bis(2-hydroxyethyl)terephthalate, comprising: (1) mixing recovered bis(2-hydroxyethyl)terephthalate obtained by depolymerization of waste polyester with a solvent to prepare a recovered bis(2-hydroxyethyl)terephthalate solution having a concentration of 95% by weight or less; and (2) storing the recovered bis(2-hydroxyethyl)terephthalate solution at a temperature of 120°C or less to maintain a YID index of 2 or less as defined below: YID index = (YID - YID [Day 0]) / YID [Day 0] Here, YID[day 0] is the yellowness index of the bis(2-hydroxyethyl)terephthalate solution recovered 30 minutes after the preparation in step (1), and YID is the yellowness index of the bis(2-hydroxyethyl)terephthalate solution recovered after storage in step (2).
2. The storage method of the recovered bis(2-hydroxyethyl)terephthalate according to claim 1, wherein: The color change index is 3 or less according to the following equation: Color change index = Col L-b [Day 0] – Col L-b Among them, Col L-b [Day 0] is a value obtained by subtracting the b value from the L value in the Hunter Lab color space of the first polyester resin injection-molded product, the first polyester resin injection-molded product being produced by using the recycled bis(2-hydroxyethyl)terephthalate itself without mixing it with a solvent and storing it, Col L-b is a value obtained by subtracting the b value from the L value in the Hunter Lab color space of the second polyester resin injection-molded product, the second polyester resin injection-molded product being prepared by using the recycled bis(2-hydroxyethyl)terephthalate after being mixed with a solvent and stored in steps (1) and (2), and The first and second polyester resin injection-molded products having a thickness of 6 mm were prepared under the same polymerization and injection-molding conditions except that each bis(2-hydroxyethyl)terephthalate was used.
3. The storage method of the recovered bis(2-hydroxyethyl)terephthalate according to claim 1, wherein: The purity of the recovered bis(2-hydroxyethyl)terephthalate used in step (1) is 60% or more, and the purity change according to the following equation is 20% or less: Purity change = rBHET purity [day 0] - rBHET purity wherein rBHET purity [Day 0] is the purity of the recovered bis(2-hydroxyethyl)terephthalate before mixing with the solvent in step (1), and rBHET purity is the purity of the recovered bis(2-hydroxyethyl)terephthalate obtained by evaporating the solvent in the solution after storage in step (2).
4. The storage method of the recovered bis(2-hydroxyethyl)terephthalate according to claim 1, wherein: The solvent includes at least one of water and ethylene glycol.
5. The storage method of recovered bis(2-hydroxyethyl)terephthalate according to claim 1, wherein: The mixing temperature in step (1) is 60°C to 120°C.
6. The method for storing the recovered bis(2-hydroxyethyl)terephthalate according to claim 1, wherein: The storage pressure in step (2) is 2kgf / cm 2 or lower.
7. The method for storing the recovered bis(2-hydroxyethyl)terephthalate according to claim 1, wherein: The storage period in step (2) is 7 days or less.
8. A method for preparing a polyester resin, comprising polymerizing a polyester resin using the recycled bis(2-hydroxyethyl)terephthalate stored according to the method of claim 1.
9. A polyester resin comprising the recycled bis(2-hydroxyethyl)terephthalate stored according to the method of claim 1.
10. The polyester resin according to claim 9, wherein The content of recycled bis(2-hydroxyethyl)terephthalate in the polyester resin is 10 wt % to 99 wt %.
11. The polyester resin according to claim 9, wherein The polyester resin contains at least one catalyst selected from metal oxides and acetates, and the metal is selected from one or more of the group consisting of antimony (Sb), titanium (Ti), germanium (Ge), manganese (Mn), cobalt (Co), tin (Sn) and calcium (Ca).
12. The polyester resin according to claim 9, wherein The polyester resin comprises a diacid component and a diol component, The diacid component comprises at least one selected from the group consisting of terephthalic acid, isophthalic acid, dimethyl isophthalate, phthalic acid, dimethyl phthalate, phthalic anhydride, 2,6-naphthalene dicarboxylic acid, dimethyl 2,6-naphthalene dicarboxylate, diphthalic acid, 1,4-cyclohexane dicarboxylic acid, 1,3-cyclohexane dicarboxylic acid, dimethyl 1,4-cyclohexane dicarboxylate, dimethyl 1,3-cyclohexane dicarboxylate, sebacic acid, succinic acid, isodecyl succinic acid, maleic acid, maleic anhydride, fumaric acid, adipic acid, glutaric acid, and azelaic acid, and The diol component includes at least one selected from the group consisting of isosorbide, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propylene glycol, 2-methylene-1,3-propylene glycol, 2-ethyl-1,3-propylene glycol, 2-isopropyl-1,3-propylene glycol, 2,2-dimethyl-1,3-propylene glycol, 1,4-butylene glycol, 2,3-butylene glycol, 3-methyl-1,5-pentanediol, 3-methyl-2,4-pentanediol, 1,6-hexanediol, 1,2-cyclohexanediol, 1,4-cyclohexanediol, diethylene glycol, 4-(hydroxymethyl)cyclohexylmethyl-4-(hydroxymethyl)cyclohexanecarboxylate, and 4-(4-(hydroxymethyl)cyclohexylmethoxymethyl)cyclohexylmethanol.
13. The polyester resin according to claim 9, wherein The polyester resin has an intrinsic viscosity (IV) at 35° C. of 0.5 to 1.2 dl / g.
14. An article comprising the polyester resin according to any one of claims 9 to 13.
15. The article of claim 14, wherein: The product is a film, a sheet or a profile.
Citation Information
Patent Citations
Crystallizing method and apparatus thereof for chemical recycling waste polyester
KR101386683B1
Processes for the purification of bis(2-hydroxyethyl)terephthalate
US7211193B2